Penyelesaian Masalah Penugasan dengan Algoritma Genetika - Zainudin Zukhri (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
The object of this research is to solve assignment problem (AP) with geneticalgorithm. The AP is solved by travelling salesman problem (TSP) approach. It can be done,because there is a similarity between representation of AP solution and representation TSPsolution. There are two operators in TSP can be applied in AP, those are crossover operatorand mutation operator. The experiments show that TSP approach can find the solutions ofAP. In this research, the Genetic Algorithm is implemented with order crossover andreciprocal exchange mutation. According to this research, it can be concluded that thesoftware with modification of genetic algorithm to solve TSP, can give alternative optimumsolution of AP.Keywords: assignment problem, crossover, genetic algorithm, mutation, travellingsalesman problem.